ANALISIS TERJADINYA RESTATEMENT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dian Oktarina; Erida Herlina (Fakultas Ekonomi dan Bisnis, 2021)
The purpose of this study is to analyze the type of restatement carried out by the company. This study uses a qualitative research design with secondary data collection methods through the Indonesia Stock Exchange website. The unit of analysis of this research is companies listed on the Indonesia Stock Exchange which restate the company's 2017-2019. The data analysis technique used in this research is descriptive-qualitative. The results showed that of the 105 data companies that did the restatement, there were 52 data companies did the restatement due to the adoption of certain PSAK and / or ISAK, 26 data of the company did the restatement because there were changes in ownership including acquisition, purchase, sale of shares, and 27 company data conducts restatement due to the correction of recording / calculation / adjustment / recognition errors. This research has a limitation that is the very high adjustment of researchers because not all companies in the financial statements published on the IDX show the reasons for the companies to do restatement. Suggestions for further researchers are advised to use data restatement in the form of quantitative data so as to minimize the researchers' adjustment.